The concept and formation pathways of human-smart object attachment: a case study of wearable smart objects - Guo, Wenxi; Chen, Haiquan; Peng, Shuyun (Frontiers in Computer Science, 2025)
With the rapid development of artificial intelligence, the Internet of Things, and related technologies, human-smart object relationships have become increasingly diversified. As smart object become deeply embedded in human society, this has given rise to emerging ethical issues—particularly human-smart object attachment—whose characteristics and influencing pathways remain unclear. This study focuses on the context of wearable smart devices and adopts a two-stage mixed-methods approach: First, based on assemblage theory and existing literature, we construct a three-phase theoretical framework encompassing human-smart object assemblage formation, experience, and attachment. Subsequently, using grounded theory, we conduct in-depth interviews with users of wearable smart objects and employ a three-tier coding process to clarify the conceptualization, typology, and formation pathways of human-smart object attachment. The findings reveal that human-smart object attachment is essentially a psychological bond formed through “self-extension” and “self-expansion,” facilitated by human-smart object capability synergy. It encompasses cognitive, affective, and conative dimensions and is influenced by three key factors: the user, the smart object, and the interaction process. Furthermore, the study explores the impact of human-smart object attachment on user attitudes and behaviors. As a unique phenomenon, the complexity of human-smart object attachment calls for HCI scholars to adopt multidisciplinary perspectives to investigate its mechanisms and effects. Such insights can assist enterprises and communities in developing technology products that better align with user needs.